Monitoring and analysis of reinforced concrete plate-column structures under room temperature and fire based on acoustic emission - Dongye Wang; Yuli Dong; Dashan Zhang; Weihua Wang; Xin Lu (Fracture and Structural Integrity)
This paper attempts to disclose the damage mechanism of reinforced concrete plate-column structures under room temperature and fire. Several tests were carried out to record the law of crack development on the plate surface under room temperature. The infrared detection technology was adopted to observe how cracks develop under fire. The acoustic emission (AE) signals at different positions of the specimen were monitored by the AE techniques. Coupled with the macroscopic test phenomena, several characteristic parameters collected by the AE system, namely, cumulative number of events, event rate, energy rate and b-value, were analyzed in details. The results show that: the cumulative number of events was active in the loading, heating and cooling stages; the crack density and the change of internal forces could be derived from the trend of event rate; the local energy changes of the specimen could be deciphered from the curves of energy rate and b-value, making it possible to judge if a component has reached the failure state; the specimen suffered the most severe damage, when the AE parameters suddenly changed; AE monitoring enables the early warning of fire to reinforced concrete plate-column structure; infrared detection technology is suitable for real-time monitoring of crack development under high temperature.